Approximation of Capacity in MIMO Systems - V. P. Tuzlukov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
This paper introduces functional approximations to the MIMO capacity over flat Rayleigh fading channels, which allow for analytical solutions to network resource optimization problems. This approximation allows to solve the problem of resource allocation optimization in radio networks and in other systems used to transfer information. The precision of the suggested approximations is assessed and is shown to provide a very close match to the exact capacity expression.